Evolution of the Palaeozoic basement of the North Patagonian Andes in the San Martín de los Andes area (Neuquén, Argentina): petrology, age and correlations - Serra Varela, Samanta (2019)
In San Martín de los Andes area (Argentinian Patagonia) the Palaeozoic basement consists of metamorphic and plutonic rocks. The metamorphic rocks include strongly deformed schists, gneisses and migmatites. Their geochemical and petrographic characteristics suggest that the protholith could have been a sequence of pelites and greywackes. Detrital zircon analysis (U-Pb Q-ICP-LA-MS) yielded a maximum depositional age of 501±14 Ma (Series 3 Cambrian) for this sedimentary protolith. Metasedimentary rocks are affected by a regional foliation defined by the minerals of the metamorphic peak. This is a S2 foliation, since relics of a former foliation are present in some samples. This regional foliation is locally affected by open folds that develop an incipient crenulation cleavage (S3). The high-grade metamorphism includes partial melting processes, where the incipient segregates intrude parallel to the regional foliation and also cut it in presence of abundant melt. Zircons from anatectic granites formed during this partial melting process yielded a U-Pb Concordia age of 434.1±4.5 Ma (Llandovery-Wenlock, Silurian). The age of maximum sedimentation and the anatectic age constrain the metamorphic evolution of the basement into the lower Palaeozoic (between upper Cambrian and lower Silurian). The igneous rocks of the basement are granodiorites, tonalities, and some gabbros that cut the metamorphic basement and contain xenoliths and roof pendants from the country rocks. These plutonic rocks are affected by low-grade metamorphism, with the development of discrete, centimetric to hectometric, brittle-ductile shear zones. The age of these igneous rocks has been constrained through U-Pb zircons analysis, carried out by several authors between ca. 370 and 400 Ma (Devonian). The maximum sedimentation age for the protolith and its metamorphic evolution seems to be related to an early Palaeozoic orogenic event, probably the Patagonian Famatinian orogeny. In contrast, the Devonian igneous rocks of San Martín de los Andes could represent a Devonian magmatic arc, related to subduction processes developed at the beginning of the Gondwanan orogenic cycle, which culminates with the Gondwanan orogeny.